Pengaruh Store Atmosphere Dan Faktor Sosial Terhadap Emosi Positif Konsumen Produk Zara Store Di Pakuwon Mall Surabaya - Sausan Defari (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2020)
The following research analyzes the effect of store atmosphere and social factors on positive consumer emotions. This study uses quantitative analysis techniques with multiple linear regression analysis models. Data collection was carried out using a questionnaire media that was distributed to respondents taken at random as many as one hundred customers who visited the ZARA STORE counter at Pakuwon Mall Surabaya. Based on the results of data calculations, it shows that: first, all independent variables (X) have a partial and simultaneous influence on the dependent variable (Y). Second, the t-test results of the store atmosphere variable (X1) show that the store atmosphere has a partial effect on positive consumer emotions (Y) and the social factor variable (X2) partially influences Consumer Positive Emotions (Y). In addition, the simultaneous influence analysis of the two independent variables (X) on the dependent variable (Y) and get a result that is Fcalculation is greater than Ftable so the variables X proved to have a simultaneous effect on the Y variable. The results of the analysis This has supported several opinions derived from several previous studies which explained that the store environment is a character or element that must be considered by business people so as to form an image that will be attached to a brand and affect the emotions of customers or consumers who play a role in forming positive influences and significant impact on consumer impulsive buying behavior